Impact of Employer Branding On Employee Loyalty – An Agenda for Enquiry - Vedagiri, Rekha; Latridis, Prof. George (The journal of contemporary issues in business and government, 2023)
The growing competitiveness between businesses in the industry is being fuelled by the shortage of talent and the increased need for highly qualified workers. Attracting and retaining skilled workers has become top-most priority of the organizations across the industry as skilled workers often help organizations achieve sustainable competitive advantage. Employer branding is often referred to the process of establishing and upholding a favourable perception of a business as a desirable place to work with the aim of attracting and retaining top talent. Employee loyalty refers to the level of commitment and attachment an employee has to their organization. The outcomes of employee loyalty are numerous and can positively impact both the individual employee and the organization. The present research study aims at building and presenting a conceptual model elucidating the impact of employer branding on employee loyalty.